PENGARUH FASILITATOR FERMENTASI DAN SUHU PENGERINGAN TERHADAP KUALITAS BIJI KAKAO - Baihaqi Baihaqi; Rita Hayati; Yusya' Abu Bakar (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2016)
The purpose of this research was to determine the effects of various fermentation facilitators and the drying temperature in producing quality cocoa beans. It also aimed to understand the effects of the addition of fermentation facilitators and drying temperature on the quality of cocoa beans as well as the interactions between the two studied factors. The research was performed at the Service Technical Implementation Unit (UPTD) of the Saree Horticulture Seed Center, Lembah Seulawah District, Aceh Besar Regency, and the Plant Pathology and Crop Analysis Laboratories of the Faculty of Agriculture of Syiah Kuala University. The study was carried out from August to October 2015. This research was conducted using a Randomized Block Design (RBD) of a 3 x 3 factorial design with three repetitions. The tested factors were: Fermentation Factor (F), with levels consisted of = F0: Natural Fermentation, F1: Fermentation using Saccharomyces cerivisiae at day 0, F2: Fermentation using Saccharomyces cerivisiae at day 1, and Drying Temperature Factor (T), with levels consisted of = T0: Sun Drying, T1: Oven Drying at 50oC, T2: Oven Drying at 60oC. The observed variables were: acidity level (pH), water content and fat content. The fermentation facilitators affected the speed of fermentation and quality of cocoa beans. The drying temperature affected the quality of cocoa beans. The interaction between fermentation facilitators and drying temperature can decrease the beans’ water content, acid total, and increase their fat content.